Deep nourishing hair conditioner and preparation method thereof

By adopting charge gradient design and intelligent release technology in the conditioner, combined with temperature-controlled liposomes and conductive microsheets, a full-dimensional hair care effect is achieved, solving the technical bottleneck of existing conditioners in repairing perming and dyeing damage and improving dryness and frizz.

CN119857064AActive Publication Date: 2025-04-22广州市芊彩化妆品有限公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510356073.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

The existing conditioners have technical bottlenecks in repairing perming and dyeing damage and improving dryness and frizziness, and are particularly difficult to achieve full-dimensional coordination of "softness-moisturizing-repair", and the intelligent release, deep penetration and long-term maintenance of active ingredients are not effective.

Method used

The "soft-moisture" composite network is constructed through charge gradient design, and the temperature-controlled poly(N-isopropylacrylamide-co-acrylic acid) is used to coat liposomes and polyaniline nanofiber composite conductive microsheets to achieve intelligent release and deep penetration of active ingredients.

Benefits of technology

It achieves a full-dimensional hair care effect from surface protection to deep repair, significantly improving the flexibility, moisturizing and repair efficiency of the conditioner, and solving the problems of intelligent release, deep penetration and long-term maintenance of active ingredients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857064A_ABST
    Figure CN119857064A_ABST
Patent Text Reader

Abstract

The invention provides a deep nourishing hair conditioner and a preparation method thereof, and belongs to the field of hair conditioners. The hair conditioner is prepared from the following chemical components: 2 to 4 percent of quaternized sodium alginate, 1 to 3 percent of polyquaternized ammonium salt, 1 to 3 percent of phosphorylated wheat protein, 0.5 to 2 percent of polyethylene glycol-150 distearate, 5 to 6 percent of temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposome, 0.1 to 0.3 percent of polyaniline nanofiber composite conductive microchip, 1.5 to 2.5 percent of glycosylglycerol, 0.5 to 1.5 percent of acetylated hyaluronic acid, less than or equal to 0.2 percent of pH regulator, 1 to 3 percent of emulsifier, 7 to 9 percent of thickening agent and the balance of water. The cleaning agent comprises the following components in percentage by weight: 2-4% of a lubricant, 0.5-0.7% of a preservative, 0.3-0.5% of an aromatic and the balance of deionized water The hair conditioner realizes a full-dimensional hair care effect from surface protection to deep repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of hair conditioners, and in particular to a deep nourishing hair conditioner and a preparation method thereof. Background Art

[0002] The main function of hair conditioner is to protect and nourish hair, help repair hair quality, and make hair smoother and smoother. As consumers' demand for the functions of hair care products increases, traditional hair conditioners are gradually showing technical bottlenecks in repairing damage caused by perming and dyeing, and improving dry and frizzy hair.

[0003] In the existing technology, hair conditioners mainly use cationic surfactants (such as quaternary ammonium salts) to neutralize the negative charge of hair to reduce static electricity, and rely on silicone oil ingredients to enhance smoothness. However, this type of formula has the following defects: traditional cationic conditioners (such as polyquaternium-10) are prone to excessive deposition on the surface of hair, causing hair to be stiff and sticky to the touch, and are not compatible with anionic moisturizing ingredients (such as hydrolyzed protein), which can easily cause flocculation; conventional moisturizers (such as hyaluronic acid) are difficult to penetrate the hair scales due to their large molecular weight (>100 kDa), and can only form a water-locking film on the surface, and cannot penetrate deep into the cortex to repair keratin breaks; existing liposome or microcapsule technology is mostly single-response (temperature or pH), which cannot match hair care scenarios (such as hair heating, slightly acidic environment of the scalp), resulting in an active ingredient release rate of less than 60%. Therefore, in response to the demand for perming and dyeing hair repair, the market urgently needs a conditioner that can break through the surface effect and achieve full-dimensional synergy of "softening-moisturizing-repairing", especially to solve the problems of intelligent release, deep penetration and long-term maintenance of active ingredients. Summary of the invention

[0004] The present application provides a deeply nourishing conditioner and a preparation method thereof, so as to realize a conditioner with full-dimensional synergy of "softening-moisturizing-repairing", especially solving the problems of intelligent release, deep penetration and long-term maintenance of active ingredients.

[0005] In a first aspect, the present application provides a deeply nourishing conditioner, which is composed of the following chemical components by mass fraction: quaternized sodium alginate: 2-4%, polyquaternium salt: 1-3%, phosphorylated wheat protein: 1-3%, polyethylene glycol-150 distearate: 0.5-2%, temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposomes: 5-6%, polyaniline nanofiber composite conductive microsheets: 0.1-0.3%, glycerol glucoside: 1.5-2.5%, acetylated hyaluronic acid: 0.5-1.5%, pH regulator ≤0.2%, emulsifier: 1-3%, thickener: 7-9%, lubricant: 2-4%, preservative: 0.5-0.7%, fragrance 0.3-0.5%, and the balance is deionized water; The temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-coated liposomes contain keratin peptides and tea tree oil in the liposomes; The polyaniline nanofiber composite conductive microsheet contains a polyethylene glycol-polylactic acid coating layer.

[0006] Optionally, the quaternary ammonium substitution degree of the quaternary ammonium sodium alginate ranges from 60% to 80%, and the molecular weight ranges from 500,000 to 800,000 Da; The polyquaternium salt is polyquaternium-67, and the cationic charge density is 0.8 to 1.2 meq / g; The phosphorylation substitution degree of phosphorylated wheat protein is ≥15% and the molecular weight is 10-30 kDa; The HLB value of polyethylene glycol-150 distearate is 8-10.

[0007] Optionally, the liposome particle size of the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposome is 80-120 nm, the coating layer thickness is 8-15 nm, and the mass ratio of keratin peptide and tea tree oil encapsulated in the liposome is (1-3):1.

[0008] Optionally, the nanofiber diameter of the polyaniline nanofiber composite conductive microsheet is 50-80 nm, the length is 1-3 μm, the conductivity is ≥20 S / cm, and the thickness of the polyethylene glycol-polylactic acid coating layer is 200-500 nm.

[0009] Optionally, the pH adjuster is citric acid or lactic acid; The emulsifier is PEG-40 hydrogenated castor oil; The thickener is composed of xanthan gum and magnesium aluminum silicate, and the mass ratio of the xanthan gum to the magnesium aluminum silicate is 1:(1-3); The lubricant is dimethyl silicone oil; The preservative consists of phenoxyethanol and ethylhexylglycerin, and the mass ratio of the phenoxyethanol to the ethylhexylglycerin is 1:(1-3); The aromatic agent is natural plant essential oil embedded in beta-cyclodextrin.

[0010] In a second aspect, the present application provides a method for preparing the deep nourishing conditioner according to any one embodiment of the first aspect, the method comprising: Obtaining the raw materials of the hair conditioner; Under stirring, adding the quaternized sodium alginate, the glycerol glucoside, the acetylated hyaluronic acid, the polyquaternium salt and the phosphorylated wheat protein into deionized water at a set temperature, and keeping the temperature to obtain an aqueous phase mixture; heating the polyethylene glycol-150 distearate, the emulsifier and the lubricant to a molten state to obtain an oil phase mixed liquid; The aqueous phase mixed liquid and the oil phase mixed liquid are subjected to high-speed homogenization treatment, and a thickener is added to obtain a first emulsion mixed liquid; Adding the temperature-controlled poly(N-isopropylacrylamide-co-acrylic acid)-coated liposomes and the polyaniline nanofiber composite conductive microsheet to the first emulsion mixture to obtain a second emulsion mixture; The pH regulator, the preservative and the fragrance are added to the second emulsion mixture to obtain the hair conditioner.

[0011] Optionally, the pressure of the high-speed homogenization treatment is 5000-8000 psi, the number of cycles is 3-5 times, and the particle size of the emulsion after homogenization is ≤5 μm.

[0012] Optionally, the preparation method of the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposomes comprises: Linseed oil, lecithin and cholesterol were added into chloroform and then rotary evaporated to obtain lipid film; Dissolving keratin peptide and tea tree oil in phosphate buffer to obtain a hydrated solution; Under a nitrogen atmosphere, the hydration solution is added to the lipid membrane, followed by high-pressure homogenization to obtain liposomes; Under stirring, the liposome is added to a copolymer solution of N-isopropylacrylamide and acrylic acid, so that the copolymer is self-assembled on the surface of the liposome to obtain the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposome.

[0013] Optionally, the mass ratio of the flaxseed oil, the lecithin and the cholesterol is 7:(1-3):1; The mass concentration of the keratin peptide is 1-3%, and the mass concentration of the tea tree oil is 0.5-1.5%; The molar ratio of the N-isopropylacrylamide to the acrylic acid is 85:15; The mass ratio of the liposome to the copolymer is 5:1.

[0014] Optionally, the method for preparing the polyaniline nanofiber composite conductive microsheet includes: The polyaniline nanofiber powder, polyethylene glycol-polylactic acid and dichloromethane are mixed to obtain a spinning solution; the mass concentration of the polyethylene glycol-polylactic acid in the spinning solution is 1-3%, and the mass ratio of the polyaniline nanofiber powder to the polyethylene glycol-polylactic acid is (1-3):1; The spinning solution is subjected to electrospinning and then pulverized to form a polyethylene glycol-polylactic acid coating layer with a set thickness on the surface of the polyaniline nanofiber to obtain the polyaniline nanofiber composite conductive microsheet; the voltage of the electrospinning is 18 to 20 kV, the propulsion rate is 0.7 to 0.9 mL / h, and the receiving distance is 10 cm.

[0015] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art: The present application provides a deeply nourishing conditioner, which rationally designs the chemical composition of the conditioner and has a multi-dimensional synergistic mechanism. First, the charge gradient is designed to form a Zeta potential gradient of quaternized sodium alginate (+15mV) → polyquaternium-67 (+5mV) → phosphorylated wheat protein (-25mV). This reduces the stiffness of the hair caused by excessive adsorption of cations, and at the same time constructs a "soft-moisturizing" composite network through electrostatic cross-linking. Secondly, when the hair is blown or the environment is heated to 40°C, the liposome releases keratin peptides to repair the cortex. At the same time, the weakly acidic environment of the scalp (pH 5.5) releases tea tree oil to inhibit Malassezia (inhibition rate ≥99%). In addition, the conductive microchip microcurrent drives the migration of charged components. Finally, glyceryl glucoside quickly penetrates and replenishes water, and acetylated hyaluronic acid locks water to form a film. At the same time, keratin peptides fill the defects of hair scales and the cross-linking density of disulfide bonds is increased. This creates a conditioner that works in all dimensions of "softening-moisturizing-repairing", and in particular solves the problems of intelligent release, deep penetration and long-term maintenance of active ingredients. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings herein are incorporated in and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the description, are used to explain the principles of the present application.

[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0018] Figure 1 A schematic flow chart of a method for preparing a deep nourishing conditioner provided in an embodiment of the present application. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0020] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0021] In a first aspect, the present application provides a deeply nourishing conditioner, which is composed of the following chemical components by mass fraction: quaternized sodium alginate: 2-4%, polyquaternium salt: 1-3%, phosphorylated wheat protein: 1-3%, polyethylene glycol-150 distearate: 0.5-2%, temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposomes: 5-6%, polyaniline nanofiber composite conductive microsheets: 0.1-0.3%, glycerol glucoside: 1.5-2.5%, acetylated hyaluronic acid: 0.5-1.5%, pH regulator ≤0.2%, emulsifier: 1-3%, thickener: 7-9%, lubricant: 2-4%, preservative: 0.5-0.7%, fragrance 0.3-0.5%, and the balance is deionized water; The temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-coated liposomes contain keratin peptides and tea tree oil in the liposomes; The polyaniline nanofiber composite conductive microsheet contains a polyethylene glycol-polylactic acid coating layer.

[0022] The conditioner achieves a full-dimensional hair care effect from surface protection to deep repair through charge gradient design, intelligent release mechanism, conductive enhanced penetration and moisturizing repair linkage. Each component works synergistically at the molecular level, breaking through the single-effect limitation of traditional formulas, and is especially suitable for hair problems such as perm and dye damage, dryness and frizziness.

[0023] The functions of each chemical component are as follows: (1) Quaternized sodium alginate (2-4%): through the quaternary ammonium group (-N⁺(CH 3 ) 3) is electrostatically bonded with the negative charge (-COO⁻) of the hair cuticle to form a continuous protective film, reducing the curling of the hair scales and reducing the friction coefficient to below 0.55. At the same time, the polyhydroxy structure of the sodium alginate main chain absorbs water through hydrogen bonds, increasing the water content of the hair (48h water retention rate ≥ 85%). In addition, the high molecular weight (500,000 to 800,000 Da) ensures the density of the film layer, prevents water evaporation, and provides a smooth surface for the subsequent penetration of active ingredients.

[0024] (2) Polyquaternium-67 (1-3%): The quaternary ammonium groups in the molecular chain are spaced far apart (charge density 0.8-1.2 meq / g), which prevents hair from becoming stiff due to excessive adsorption and forms a charge gradient with quaternized sodium alginate. At the same time, hydrophobic segments (such as long-chain alkyl groups) are embedded in the gaps of the hair scales to fill the gaps. Together with quaternized sodium alginate, a "high charge-low charge" gradient is formed to optimize the balance between softness and antistatic properties.

[0025] (3) Phosphorylated wheat protein (1-3%): phosphate group (-PO 4 ³⁻) and cationic components (quaternary ammonium salts) are electrostatically cross-linked to form a three-dimensional network to lock in moisture. At the same time, the low molecular weight (10-30 kDa) allows it to penetrate the gaps between hair scales and replenish cortical keratin (repair rate ≥ 70%). Phosphorylation enhances hydrophilicity and forms a dual-effect structure of "outer layer moisture lock-inner layer repair" with the cationic membrane layer.

[0026] (4) Polyethylene glycol-150 distearate (0.5-2%): The nonionic PEG chain isolates cations (quaternary ammonium salts) and anions (phosphorylated proteins) to prevent flocculation. At the same time, the HLB value of 8-10 balances the oil-water compatibility and ensures that the liposomes and conductive microsheets are evenly dispersed (centrifugal stability > 95%). As a "charge buffer", it ensures the long-term stability of the multi-charged components in the formula.

[0027] (5) Temperature-controlled poly(NIPAM-co-AA)-coated liposomes (5-6%): The LCST (lowest critical solution temperature) property of polyNIPAM causes the liposome membrane to shrink at the temperature of hair drying, releasing keratin peptides. At the same time, the carboxyl group of acrylic acid is protonated in a weakly acidic environment, the membrane permeability increases, and tea tree oil is released. The dual-trigger release precisely matches the hair care scenario (heating caused by hair drying + slightly acidic scalp), and keratin peptides penetrate deep into the cortex to repair disulfide bonds.

[0028] (6) Polyaniline nanofiber composite conductive microsheets (0.1-0.3%): Conductive microsheets (conductivity ≥ 20 S / cm) form a potential gradient under a microcurrent (0.5 mA), driving charged components (such as keratin peptides) to migrate to the cortex. At the same time, local temperature increase (ΔT≈5°C) accelerates liposome release and synergistically improves repair efficiency by 40%. The PEG-PLA coating layer (200-500 nm) prevents fiber oxidation and enhances compatibility with the conditioner matrix.

[0029] (7) Glyceryl glucoside (1.5-2.5%) + acetylated hyaluronic acid (0.5-1.5%): Small molecule glyceryl glucoside quickly penetrates into the gaps between hair scales and absorbs water through an osmotic pressure gradient (the water content of the stratum corneum increases by 35% in 30 minutes). At the same time, the acetyl substitution (≥85%) of acetylated hyaluronic acid enhances hydrophobicity and forms a breathable moisturizing film on the surface of the hair (water loss rate ≤15% in 48 hours). The combination of the two realizes a "dynamic hydration-long-term water lock" cycle to maintain a moist environment in the cortex.

[0030] (8) pH adjuster (citric acid / lactic acid, ≤0.2%): maintain the system pH at 5.0-5.8 to match the natural acidic environment of the scalp (pH 5.5), enhance the efficiency of cation adsorption, and prevent excessive acidification from damaging hair keratin.

[0031] (9) Emulsifier (PEG-40 hydrogenated castor oil, 1-3%): The polyethylene glycol chain (PEG-40) and the hydrophobic group of hydrogenated castor oil stabilize the oil-water interface (interfacial tension ≤ 2 mN / m) and prevent the aggregation of liposomes and conductive microsheets.

[0032] (10) Thickener (xanthan gum + magnesium aluminum silicate, 7-9%): Xanthan gum provides shear thinning properties (thixotropic index ≥ 4.0), which reduces viscosity during application and ensures uniform coverage. Magnesium aluminum silicate: layered silicate structure suspended particles (conductive microplatelet sedimentation rate <0.5%), maintaining system uniformity.

[0033] (11) Lubricant (dimethyl silicone oil, 2-4%): The low surface tension (21 mN / m) siloxane chain spreads on the hair surface, reducing the friction coefficient and reducing combing damage.

[0034] (12) Preservatives (phenoxyethanol + ethylhexylglycerin, 0.5-0.7%): Phenoxyethanol destroys microbial cell membranes, and ethylhexylglycerin inhibits biofilm formation.

[0035] (13) Fragrances (β-cyclodextrin encapsulated essential oils, 0.3-0.5%): Volatile essential oils (such as lavender) are encapsulated in the β-cyclodextrin cavity to slowly release the aroma (12h aroma retention rate ≥80%), reducing the risk of sensitization caused by direct contact.

[0036] In some embodiments, the quaternized sodium alginate has a quaternization degree of substitution ranging from 60% to 80% and a molecular weight of 500,000 to 800,000 Da; The polyquaternium salt is polyquaternium-67, and the cationic charge density is 0.8 to 1.2 meq / g; The phosphorylation substitution degree of phosphorylated wheat protein is ≥15% and the molecular weight is 10-30 kDa; The HLB value of polyethylene glycol-150 distearate is 8-10.

[0037] In some embodiments, the liposome particle size of the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposome is 80-120 nm, the coating layer thickness is 8-15 nm, and the mass ratio of keratin peptide and tea tree oil encapsulated in the liposome is (1-3):1.

[0038] In some embodiments, the nanofiber diameter of the polyaniline nanofiber composite conductive microsheet is 50-80 nm, the length is 1-3 μm, the conductivity is ≥20 S / cm, and the polyethylene glycol-polylactic acid coating layer has a thickness of 200-500 nm.

[0039] In some embodiments, the pH adjuster is citric acid or lactic acid; The emulsifier is PEG-40 hydrogenated castor oil; The thickener is composed of xanthan gum and magnesium aluminum silicate, and the mass ratio of the xanthan gum to the magnesium aluminum silicate is 1:(1-3); The lubricant is dimethyl silicone oil; The preservative consists of phenoxyethanol and ethylhexylglycerin, and the mass ratio of the phenoxyethanol to the ethylhexylglycerin is 1:(1-3); The aromatic agent is natural plant essential oil embedded in beta-cyclodextrin.

[0040] In summary, the present application provides a conditioner with a multi-dimensional synergistic mechanism, as follows: (1) Charge gradient synergy: The charge gradient is designed to form a Zeta potential gradient from quaternized sodium alginate (+15mV) → polyquaternium-67 (+5mV) → phosphorylated wheat protein (-25mV). This reduces the stiffness of hair caused by excessive adsorption of cations, while constructing a "soft-moisturizing" composite network through electrostatic cross-linking.

[0041] (2) Intelligent release synergy: When the air is blown or the environment is heated to 40°C, the liposome releases keratin peptides to repair the cortex. At the same time, the weakly acidic environment of the scalp (pH 5.5) releases tea tree oil to inhibit Malassezia (inhibition rate ≥ 99%). In addition, the microcurrent of the conductive microsheet drives the migration of charged components.

[0042] (3) Moisturizing and repairing linkage: Glyceryl glucoside quickly penetrates and replenishes moisture, while acetylated hyaluronic acid locks in moisture and forms a film. At the same time, keratin peptides fill in the defects of hair scales and increase the cross-linking density of disulfide bonds.

[0043] Figure 1 A schematic flow chart of a method for preparing a deep nourishing conditioner provided in an embodiment of the present application.

[0044] Second, as Figure 1 As shown, the present application provides a method for preparing the deep nourishing conditioner according to any one embodiment of the first aspect, the method comprising: S1, obtaining the raw materials of the hair conditioner; S2, under stirring, adding the quaternized sodium alginate, the glycerol glucoside, the acetylated hyaluronic acid, the polyquaternium salt and the phosphorylated wheat protein to deionized water with a set temperature, and keeping the temperature to obtain an aqueous phase mixture; S3, heating the polyethylene glycol-150 distearate, the emulsifier and the lubricant to a molten state to obtain an oil phase mixed liquid; S4, subjecting the aqueous phase mixed liquid and the oil phase mixed liquid to high-speed homogenization, and adding a thickener to obtain a first emulsion mixed liquid; S5, adding the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-coated liposomes and the polyaniline nanofiber composite conductive microsheet to the first emulsion mixture to obtain a second emulsion mixture; S6. Adding the pH regulator, the preservative and the fragrance into the second emulsion mixture to obtain the hair conditioner.

[0045] In some embodiments, the pressure of the high-speed homogenization process is 5000-8000 psi, the number of cycles is 3-5 times, and the particle size of the emulsion after homogenization is ≤5 μm.

[0046] In some embodiments, the method for preparing the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposomes comprises: S1, adding linseed oil, lecithin and cholesterol into chloroform, and then performing rotary evaporation to obtain a lipid film; S2, dissolving keratin peptide and tea tree oil in phosphate buffer to obtain a hydration solution; S3, under a nitrogen atmosphere, adding the hydration solution to the lipid membrane, and then performing high pressure homogenization to obtain liposomes; S4. Under stirring, adding the liposome to the copolymer of N-isopropylacrylamide and acrylic acid, so that the copolymer self-assembles on the surface of the liposome to obtain the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposome.

[0047] In some embodiments, the mass ratio of the flaxseed oil, the lecithin and the cholesterol is 7:(1-3):1; The mass concentration of the keratin peptide is 1-3%, and the mass concentration of the tea tree oil is 0.5-1.5%; The molar ratio of the N-isopropylacrylamide to the acrylic acid is 85:15; The mass ratio of the liposome to the copolymer is 5:1.

[0048] The role of limiting linseed oil: lecithin: cholesterol = 7: (1-3): 1: linseed oil can provide lipid fluidity and enhance the encapsulation rate of keratin peptides. Lecithin, as the main film-forming material, can adjust the flexibility of the membrane. Cholesterol can stabilize the lipid bilayer and reduce leakage.

[0049] The role of limiting NIPAM:AA=85:15: NIPAM can dominate the temperature sensitivity, LCST≈40℃, ensuring that the blowing temperature triggers the release. AA can provide pH response, the carboxyl group is protonated at pH 5.5, and the membrane permeability is increased by 3 times.

[0050] The ratio of liposome to copolymer is limited to 5:1. If the ratio is too low, incomplete encapsulation will occur, while if it is too high, copolymer aggregation will occur.

[0051] In some embodiments, the method for preparing the polyaniline nanofiber composite conductive microsheet comprises: Obtaining polyaniline nanofiber powder; The polyaniline nanofiber powder, polyethylene glycol-polylactic acid and dichloromethane are mixed to obtain a spinning solution; the mass concentration of the polyethylene glycol-polylactic acid in the spinning solution is 1-3%, and the mass ratio of the polyaniline nanofiber powder to the polyethylene glycol-polylactic acid is (1-3):1; The spinning solution is subjected to electrospinning and then pulverized to form a polyethylene glycol-polylactic acid coating layer with a set thickness on the surface of the polyaniline nanofiber to obtain the polyaniline nanofiber composite conductive microsheet; the voltage of the electrospinning is 18 to 20 kV, the propulsion rate is 0.7 to 0.9 mL / h, and the receiving distance is 10 cm.

[0052] This application achieves a high degree of unity between the functional design of ingredients and the coordinated optimization of processes by precisely controlling various process parameters (temperature, pressure, ratio, etc.). The interaction between parameters (such as high-pressure homogenization and refinement of emulsions, and electrospinning to regulate conductivity) ensures the intelligent release and deep penetration of active ingredients, breaking through the technical bottleneck of traditional conditioners.

[0053] In summary, the advantages of this application are mainly reflected in the following aspects: (1) Multi-dimensional hair care effect: Through charge gradient design, intelligent release mechanism and moisturizing and repair linkage, it achieves a full-dimensional hair care effect from surface protection to deep repair, breaking through the single-effect limitation of traditional conditioners.

[0054] (2) Synergy of highly effective ingredients: The various chemical ingredients work synergistically at the molecular level. For example, quaternized sodium alginate and polyquaternium salt form a charge gradient, and phosphorylated wheat protein and cationic ingredients form electrostatic cross-linking to jointly construct a "softening-moisturizing" composite network, significantly improving the hair care effect.

[0055] (3) Intelligent release technology: Temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-encapsulated liposomes can intelligently release keratin peptides and tea tree oil under specific conditions (such as hair drying and weak acidic environment of the scalp), accurately matching the hair care scene and improving the repair efficiency.

[0056] (4) Conductivity enhances penetration: Polyaniline nanofiber composite conductive microsheets use microcurrent to drive the migration of charged components, accelerate the release of liposomes, and further enhance the repair effect.

[0057] (5) Advanced preparation technology: Through advanced processes such as high-pressure homogenization to refine the emulsion and electrospinning to control conductivity, we ensure the intelligent release and deep penetration of active ingredients, and achieve a high degree of unity between ingredient functional design and process coordinated optimization.

[0058] (6) Safe and mild formula: Natural plant essential oils are used as fragrances, β-cyclodextrin is encapsulated to reduce the risk of allergies, and mild preservatives are used to ensure that the formula is safe and mild, suitable for a variety of hair problems.

[0059] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0060] Embodiment 1: This embodiment provides a deep nourishing hair conditioner, which is composed of the following chemical components by mass fraction: Quaternized sodium alginate: 2% (degree of substitution 60%, molecular weight about 500,000 Da); Polyquaternium-67: 1% (charge density 0.8 meq / g); Phosphorylated wheat protein: 1% (degree of substitution 15%, molecular weight approximately 10 kDa); PEG-150 distearate: 0.5% (HLB 8); Temperature-controlled poly(NIPAM-co-AA)-coated liposomes: 5% (particle size 80 nm, coating layer thickness 8 nm, keratin peptide: tea tree oil = 1:1); Polyaniline nanofiber composite conductive microsheets: 0.1% (diameter 50 nm, length 1 μm, conductivity 20 S / cm, coating layer 200 nm); Glyceryl glucoside: 1.5%, acetylated hyaluronic acid: 0.5%; pH adjuster (citric acid): 0.1%; Emulsifier (PEG-40 hydrogenated castor oil): 1%; Thickener (xanthan gum: magnesium aluminum silicate = 1:1): 7%; Lubricant (dimethyl silicone oil): 2%; Preservatives (phenoxyethanol: ethylhexylglycerin = 1:1): 0.5%; Aromatherapy agent (lavender essential oil encapsulated in β-cyclodextrin): 0.3%; Balance: deionized water.

[0061] At the same time, based on the above-mentioned hair conditioner, this embodiment also provides a method for preparing the hair conditioner, which comprises the following steps: (1) obtaining the raw materials of the hair conditioner; (2) adding the quaternized sodium alginate, the glycerol glucoside, the acetylated hyaluronic acid, the polyquaternium salt and the phosphorylated wheat protein into deionized water at 70° C. with a stirring speed of 400 rpm, and keeping the mixture warm for 60 minutes to obtain an aqueous phase mixture; The preparation method of the quaternized sodium alginate is as follows: dissolving sodium alginate in deionized water (concentration 8%), adding NaOH to adjust the pH to 11; adding 3-chloro-2-hydroxypropyltrimethylammonium chloride (dissolved in an equal volume of water), controlling the temperature at 60°C, stirring at 300 rpm, and reacting for 6 hours to obtain quaternized sodium alginate; The preparation method of the phosphorylated wheat protein is as follows: hydrolyzed wheat protein (McLean Biochemical, molecular weight of about 10 kDa, purity> 90%) is mixed with sodium tripolyphosphate and deionized water, the pH is adjusted to 9.2, and the mixture is stirred at a constant temperature of 50° C. until the amount of amino group reduction corresponds to a degree of substitution of 15%, thereby obtaining the phosphorylated wheat protein; (3) heating the polyethylene glycol-150 distearate, the emulsifier and the lubricant to 60° C. to obtain a molten oil phase mixture; The preparation method of polyethylene glycol-150 distearate is as follows: feed PEG-150:stearic acid = 1:2.2 (molar ratio), add a catalyst (PTSA 1%); then heat to 150°C, stir and react for 8 hours under nitrogen protection, remove the generated water through a water separator, and obtain polyethylene glycol-150 distearate; (4) subjecting the aqueous phase mixed liquid and the oil phase mixed liquid to high-speed homogenization and adding a thickener to obtain a first emulsion mixed liquid; The high-speed homogenization process has a pressure of 5000 psi, a cycle number of 5 times, and an emulsion particle size of ≤5 μm after homogenization; (5) adding the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-coated liposomes and the polyaniline nanofiber composite conductive microsheet to the first emulsion mixture to obtain a second emulsion mixture; The preparation method of the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposomes includes: dissolving 7 g of linseed oil, 1 g of lecithin, and 1 g of cholesterol in 50 mL of chloroform, and then ultrasonically treating (40 kHz, 15 minutes) until completely dissolved, and transferring to a rotary evaporator to obtain a lipid film; dissolving 1 g of keratin peptide (Jianchu Biology, CAS: 69430-36-0) and 1 g of tea tree oil (tea tree essential oil of Jiangxi Wanlv Natural Flavor Co., Ltd., effective substance content: 99%, CAS: 68647-73-4) in 100 mL of phosphate buffer, and magnetically stirring (500 rpm, 30 minutes) until uniform, and then ultrasonically treating (40 kHz, 10 minutes) to ensure that the oil phase is dispersed into nanoemulsion droplets to obtain a hydrated solution; adding the hydrated solution to a flask containing the lipid film, controlling the temperature to 55±1°C under nitrogen protection, and magnetically stirring (300 rpm, 30 minutes) until uniform, then high pressure homogenization at a homogenization pressure of 15,000 psi, and the number of cycles: 3 times to obtain liposomes; N-isopropylacrylamide and acrylic acid with a molar ratio of 85:15 were dissolved in deionized water (concentration 10% w / v), ammonium persulfate (APS, monomer:APS = 1:1.2, molar ratio) was added, and the temperature was raised to 70°C under nitrogen protection, and stirred for reaction for 12 hours to obtain a copolymer; 5g of the liposome was dispersed in a dichloromethane solution of 1g of the copolymer (concentration 1 mg / mL) under stirring (300 rpm), the temperature was controlled at 45±1°C (higher than LCST), magnetic stirring was performed (100 rpm, 2h), and centrifugal purification (10,000 rpm, 20 minutes) was performed to remove the unabsorbed copolymer, so that the copolymer was self-assembled on the surface of the liposome to obtain the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposome; The preparation method of the polyaniline nanofiber composite conductive microsheet comprises: placing a reaction kettle in an ice-salt bath, controlling the system temperature at 0-5°C, adding 200 mL of deionized water and 1.5 g of DBSA, stirring until completely dissolved, then adding 2.5 g of aniline monomer, magnetically stirring (500 rpm, 30 minutes) to form an aniline-DBSA complex, dissolving 5.0 g of APS in precooled water (0°C), slowly dripping into the reaction system (drip rate 1 mL / min), maintaining the temperature at 0-5°C, reacting for 24 hours, the solution changes from colorless to dark green, and then purifying to obtain polyaniline nanofiber powder; dissolving 1 g of polyaniline nanofiber powder and 1 g of polyethylene glycol-polylactic acid (Pluronic® PE 6800) in 100 mL of dichloromethane, magnetically stirring (40°C, 2 hours), and ultrasonically treating (40 kHz, 30 minutes) until uniformly dispersed to obtain a spinning solution; loading the spinning solution into a syringe (needle diameter 0.6 mm), start the high-voltage power supply and the propulsion pump, continue spinning until the film thickness is 500 μm, collect the fiber film, the voltage of the electrospinning is 18 kV, the propulsion rate is 0.7 mL / h, the receiving distance is 10 cm, the fiber film is cut into pieces and put into the air flow mill (pressure 0.8 MPa), the crushing time is 10 minutes, and the film is sieved with 200 mesh (pore size 75 μm) to obtain the polyaniline nanofiber composite conductive microsheet; (6) adding the pH adjuster, the preservative and the fragrance to the second emulsion mixture to obtain the hair conditioner; The preparation method of the fragrance comprises: dissolving β-cyclodextrin (purity ≥ 98%, degree of substitution ≥ 6.0) in deionized water at 60°C with a concentration of 12% (w / v); mixing lavender essential oil (model: Givaudan Lavender Oil LIS 3256) and β-cyclodextrin in a ratio of 1:2 (mass ratio), controlling the temperature at 60±2°C, magnetically stirring (500 rpm) for 4 hours, and then adjusting the pH to 2.5-3.5 with dilute hydrochloric acid to enhance the inclusion stability, thereby obtaining the fragrance.

[0062] Embodiment 2: This embodiment provides a deep nourishing hair conditioner, which is composed of the following chemical components by mass fraction: Quaternized sodium alginate: 3% (substitution degree 70%, molecular weight about 650,000 Da); Polyquaternium-67: 2% (charge density 1.0 meq / g); Phosphorylated wheat protein: 2% (substitution degree 20%, molecular weight approximately 20 kDa); PEG-150 distearate: 1.2% (HLB 9); Temperature-controlled poly(NIPAM-co-AA)-coated liposomes: 5.5% (particle size 100 nm, coating layer thickness 12 nm, keratin peptide: tea tree oil = 2:1); Polyaniline nanofiber composite conductive microsheets: 0.2% (diameter 65 nm, length 2 μm, conductivity 25 S / cm, coating layer 350 nm); Glyceryl Glucoside: 2.0%, Acetylated Hyaluronic Acid: 1.0%; pH adjuster (lactic acid): 0.15%; Emulsifier (PEG-40 hydrogenated castor oil): 2%; Thickener (xanthan gum: magnesium aluminum silicate = 1:2): 8%; Lubricant (dimethyl silicone oil): 3%; Preservatives (phenoxyethanol: ethylhexylglycerin = 1:2): 0.6%; Aromatherapy agent (lavender essential oil encapsulated in β-cyclodextrin): 0.4%; Balance: deionized water.

[0063] At the same time, based on the above-mentioned hair conditioner, this embodiment also provides a method for preparing the hair conditioner, which comprises the following steps: (1) obtaining the raw materials of the hair conditioner; (2) adding the quaternized sodium alginate, the glycerol glucoside, the acetylated hyaluronic acid, the polyquaternium salt and the phosphorylated wheat protein into deionized water at 70° C. with a stirring speed of 400 rpm, and keeping the mixture warm for 60 minutes to obtain an aqueous phase mixture; The preparation method of the quaternized sodium alginate is as follows: dissolving sodium alginate in deionized water (concentration 8%), adding NaOH to adjust the pH to 11; adding 3-chloro-2-hydroxypropyltrimethylammonium chloride (dissolved in an equal volume of water), controlling the temperature at 60°C, stirring at 300 rpm, and reacting for 6 hours to obtain quaternized sodium alginate; The preparation method of the phosphorylated wheat protein is as follows: hydrolyzed wheat protein (Aladdin reagent, molecular weight of about 20 kDa, purity> 90%) is mixed with sodium tripolyphosphate and deionized water, the pH is adjusted to 9.2, and the mixture is stirred at a constant temperature of 50° C. until the amount of amino group reduction corresponds to a degree of substitution of 20%, thereby obtaining phosphorylated wheat protein; (3) heating the polyethylene glycol-150 distearate, the emulsifier and the lubricant to 60° C. to obtain a molten oil phase mixture; The preparation method of polyethylene glycol-150 distearate is as follows: feed PEG-150:stearic acid = 1:2.2 (molar ratio), add a catalyst (PTSA 1%); then heat to 150°C, stir and react for 8 hours under nitrogen protection, remove the generated water through a water separator, and obtain polyethylene glycol-150 distearate.

[0064] (4) subjecting the aqueous phase mixed liquid and the oil phase mixed liquid to high-speed homogenization and adding a thickener to obtain a first emulsion mixed liquid; The high-speed homogenization process has a pressure of 6000 psi, a cycle number of 4 times, and an emulsion particle size of ≤5 μm after homogenization; (5) adding the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-coated liposomes and the polyaniline nanofiber composite conductive microsheet to the first emulsion mixture to obtain a second emulsion mixture; The preparation method of the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-coated liposomes comprises: dissolving 7 g of linseed oil, 2 g of lecithin, and 1 g of cholesterol in 50 mL of chloroform, and then ultrasonically treating (40 kHz, 15 minutes) until completely dissolved, and transferring to a rotary evaporator to obtain a lipid film; dissolving 2 g of keratin peptide and 1 g of tea tree oil in 100 mL of phosphate buffer, and magnetically stirring (500 rpm, 30 minutes) until uniform, and then ultrasonically treating (40 kHz, 10 minutes) to ensure that the oil phase is dispersed into nanoemulsion droplets to obtain a hydrated solution; adding the hydrated solution to a flask containing the lipid film, controlling the temperature to 55±1°C under nitrogen protection, magnetically stirring (300 rpm, 30 minutes) until uniform, and then homogenizing at a pressure of 15,000 psi, and the number of cycles: 3 times, to obtain liposomes; N-isopropylacrylamide and acrylic acid with a molar ratio of 85:15 were dissolved in deionized water (concentration 10% w / v), ammonium persulfate (APS, monomer:APS = 1:1.2, molar ratio) was added, and the temperature was raised to 70°C under nitrogen protection, and the reaction was stirred for 12 hours to obtain a copolymer; 5g of the liposome was dispersed in a dichloromethane solution of 1g of the copolymer (concentration 1 mg / mL) under stirring (300 rpm), the temperature was controlled at 45±1°C (higher than LCST), magnetic stirring (100 rpm, 2h), centrifugal purification (10,000 rpm, 20 minutes), and the unadsorbed copolymer was removed, so that the copolymer was self-assembled on the surface of the liposome to obtain the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposomes; The preparation method of the polyaniline nanofiber composite conductive microsheet comprises: placing a reaction kettle in an ice-salt bath, controlling the system temperature at 0-5°C, adding 200 mL of deionized water and 1.5 g of DBSA, stirring until completely dissolved, then adding 2.5 g of aniline monomer, magnetically stirring (500 rpm, 30 minutes) to form an aniline-DBSA complex, dissolving 5.0 g of APS in precooled water (0°C), slowly dripping into the reaction system (drip rate 1 mL / min), maintaining the temperature at 0-5°C, reacting for 24 hours, the solution changes from colorless to dark green, and then purifying to obtain polyaniline nanofiber powder; dissolving 4 g of polyaniline nanofiber powder and 2 g of polyethylene glycol-polylactic acid in 100 mL of dichloromethane, magnetically stirring (40°C, 2 hours), and ultrasonically treating (40 kHz, 30 minutes) until uniform dispersion to obtain a spinning solution; loading the spinning solution into a syringe (needle diameter 0.6 mm), starting a high-voltage power supply and a propulsion pump, and continuously spinning until the film thickness is 500 μm, collecting the fiber membrane, the voltage of the electrospinning is 19 kV, the propulsion rate is 0.8 mL / h, the receiving distance is 10 cm, the fiber membrane is cut into pieces and put into a jet mill (pressure 0.8 MPa), the crushing time is 10 minutes, and the fiber membrane is sieved with 200 mesh (pore size 75 μm) to obtain the polyaniline nanofiber composite conductive microsheet; (6) adding the pH adjuster, the preservative and the fragrance to the second emulsion mixture to obtain the hair conditioner; The preparation method of the fragrance comprises: dissolving β-cyclodextrin (purity ≥ 98%, degree of substitution ≥ 6.0) in deionized water at 60°C with a concentration of 12% (w / v); mixing lavender essential oil (model: Givaudan Lavender Oil LIS 3256) and β-cyclodextrin in a ratio of 1:2 (mass ratio), controlling the temperature at 60±2°C, magnetically stirring (500 rpm) for 4 hours, and then adjusting the pH to 2.5-3.5 with dilute hydrochloric acid to enhance the inclusion stability, thereby obtaining the fragrance.

[0065] Embodiment 3: This embodiment provides a deep nourishing hair conditioner, which is composed of the following chemical components by mass fraction: Quaternized sodium alginate: 4% (degree of substitution 80%, molecular weight about 800,000 Da); Polyquaternium-67: 3% (charge density 1.2 meq / g); Phosphorylated wheat protein: 3% (degree of substitution 25%, molecular weight approximately 20 kDa); PEG-150 Distearate: 2% (HLB 10); Temperature-controlled poly(NIPAM-co-AA)-coated liposomes: 6% (particle size 120 nm, coating layer thickness 15 nm, keratin peptide: tea tree oil = 3:1); Polyaniline nanofiber composite conductive microsheets: 0.3% (diameter 80 nm, length 3 μm, conductivity 30 S / cm, coating layer 500 nm); Glyceryl glucoside: 2.5%, acetylated hyaluronic acid: 1.5%; pH adjuster (lactic acid): 0.2%; Emulsifier (PEG-40 hydrogenated castor oil): 3%; Thickener (xanthan gum: magnesium aluminum silicate = 1:3): 9%; Lubricant (dimethyl silicone oil): 4%; Preservatives (phenoxyethanol: ethylhexylglycerin = 1:3): 0.7%; Aromatherapy agent (lavender essential oil encapsulated in β-cyclodextrin): 0.5%; Balance: deionized water.

[0066] At the same time, based on the above-mentioned hair conditioner, this embodiment also provides a method for preparing the hair conditioner, which comprises the following steps: (1) obtaining the raw materials of the hair conditioner; (2) adding the quaternized sodium alginate, the glycerol glucoside, the acetylated hyaluronic acid, the polyquaternium salt and the phosphorylated wheat protein into deionized water at 70° C. with a stirring speed of 400 rpm, and keeping the mixture warm for 60 minutes to obtain an aqueous phase mixture; The preparation method of the quaternized sodium alginate is as follows: dissolving sodium alginate in deionized water (concentration 8%), adding NaOH to adjust the pH to 11; adding 3-chloro-2-hydroxypropyltrimethylammonium chloride (dissolved in an equal volume of water), controlling the temperature at 60°C, stirring at 300 rpm, and reacting for 6 hours to obtain quaternized sodium alginate; The preparation method of the phosphorylated wheat protein is as follows: hydrolyzed wheat protein (Aladdin reagent, molecular weight of about 20 kDa, purity> 90%) is mixed with sodium tripolyphosphate and deionized water, the pH is adjusted to 9.2, and the mixture is stirred at a constant temperature of 50° C. until the amount of amino group reduction corresponds to a degree of substitution of 35%, thereby obtaining the phosphorylated wheat protein; (3) heating the polyethylene glycol-150 distearate, the emulsifier and the lubricant to 60° C. to obtain a molten oil phase mixture; The preparation method of polyethylene glycol-150 distearate is as follows: feed PEG-150:stearic acid = 1:2.2 (molar ratio), add a catalyst (PTSA 1%); then heat to 150°C, stir and react for 8 hours under nitrogen protection, remove the generated water through a water separator, and obtain polyethylene glycol-150 distearate.

[0067] (4) subjecting the aqueous phase mixed liquid and the oil phase mixed liquid to high-speed homogenization and adding a thickener to obtain a first emulsion mixed liquid; The high-speed homogenization process has a pressure of 8000 psi, a cycle number of 3 times, and an emulsion particle size of ≤5 μm after homogenization; (5) adding the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-coated liposomes and the polyaniline nanofiber composite conductive microsheet to the first emulsion mixture to obtain a second emulsion mixture; The method for preparing the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-coated liposomes comprises: dissolving 7 g of linseed oil, 3 g of lecithin, and 1 g of cholesterol in 50 mL of chloroform, and then ultrasonically treating (40 kHz, 15 minutes) until completely dissolved, and transferring to a rotary evaporator to obtain a lipid film; dissolving 3 g of keratin peptide and 1 g of tea tree oil in 100 mL of phosphate buffer, and magnetically stirring (500 rpm, 30 minutes) until uniform, and then ultrasonically treating (40 kHz, 10 minutes) to ensure that the oil phase is dispersed into nanoemulsion droplets to obtain a hydrated solution; adding the hydrated solution to a flask containing the lipid film, controlling the temperature to 55±1°C under nitrogen protection, magnetically stirring (300 rpm, 30 minutes) until uniform, and then homogenizing at a pressure of 15,000 psi, and the number of cycles: 3 times, to obtain liposomes; N-isopropylacrylamide and acrylic acid with a molar ratio of 85:15 were dissolved in deionized water (concentration 10% w / v), ammonium persulfate (APS, monomer:APS = 1:1.2, molar ratio) was added, and the temperature was raised to 70°C under nitrogen protection, and the reaction was stirred for 12 hours to obtain a copolymer; 5g of the liposome was dispersed in a dichloromethane solution of 1g of the copolymer (concentration 1 mg / mL) under stirring (300 rpm), the temperature was controlled at 45±1°C (higher than LCST), magnetic stirring (100 rpm, 2h), centrifugal purification (10,000 rpm, 20 minutes), and the unadsorbed copolymer was removed, so that the copolymer was self-assembled on the surface of the liposome to obtain the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposomes; The preparation method of the polyaniline nanofiber composite conductive microsheet comprises: placing a reaction kettle in an ice-salt bath, controlling the system temperature at 0-5°C, adding 200 mL of deionized water and 1.5 g of DBSA, stirring until completely dissolved, then adding 2.5 g of aniline monomer, magnetically stirring (500 rpm, 30 minutes) to form an aniline-DBSA complex, dissolving 5.0 g of APS in precooled water (0°C), slowly dripping into the reaction system (drip rate 1 mL / min), maintaining the temperature at 0-5°C, reacting for 24 hours, the solution changes from colorless to dark green, and then purifying to obtain polyaniline nanofiber powder; dissolving 5 g of polyaniline nanofiber powder and 3 g of polyethylene glycol-polylactic acid in 100 mL of dichloromethane, magnetically stirring (40°C, 2 hours), and ultrasonically treating (40 kHz, 30 minutes) until uniform dispersion to obtain a spinning solution; loading the spinning solution into a syringe (needle diameter 0.6 mm), starting a high-voltage power supply and a propulsion pump, and continuously spinning until the film thickness is 500 μm, collecting the fiber membrane, the voltage of the electrospinning is 20 kV, the propulsion rate is 0.9 mL / h, the receiving distance is 10 cm, the fiber membrane is cut into pieces and put into a jet mill (pressure 0.8 MPa), the crushing time is 10 minutes, and the fiber membrane is sieved with 200 mesh (pore size 75 μm) to obtain the polyaniline nanofiber composite conductive microsheet; (6) adding the pH adjuster, the preservative and the fragrance to the second emulsion mixture to obtain the hair conditioner; The preparation method of the fragrance comprises: dissolving β-cyclodextrin (purity ≥ 98%, degree of substitution ≥ 6.0) in deionized water at 60°C with a concentration of 12% (w / v); mixing lavender essential oil (model: Givaudan Lavender Oil LIS 3256) and β-cyclodextrin in a ratio of 1:2 (mass ratio), controlling the temperature at 60±2°C, magnetically stirring (500 rpm) for 4 hours, and then adjusting the pH to 2.5-3.5 with dilute hydrochloric acid to enhance the inclusion stability, thereby obtaining the fragrance.

[0068] Comparative Example 1: This comparative example is modified as follows based on Example 2: Quaternized sodium alginate is not added to the conditioner.

[0069] Comparative Example 2: This comparative example is modified as follows based on Example 2: No polyquaternium is added to the conditioner.

[0070] Comparative Example 3: This comparative example is modified as follows based on Example 2: No phosphorylated wheat protein is added to the conditioner.

[0071] Comparative Example 4: This comparative example is modified as follows based on Example 2: PEG-150 distearate is not added to the conditioner.

[0072] Comparative Example 5: This comparative example is modified as follows based on Example 2: The temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-coated liposomes were not added to the conditioner, and keratin peptides and tea tree oil were added separately.

[0073] Comparative Example 6: This comparative example is modified as follows based on Example 2: The polyaniline nanofiber composite conductive microsheets are not added to the hair conditioner.

[0074] Comparative Example 7: This comparative example is modified as follows based on Example 2: Glyceryl glucoside and acetylated hyaluronic acid are not added to the conditioner.

[0075] The performance of the hair conditioners obtained in Examples 1 to 3 and Comparative Examples 1 to 7 was measured. The results are shown in Table 1. The measuring method is as follows: Friction coefficient (100 combings): TRIBOgear friction tester (ASTM D1894), load 50 g, speed 10 cm / s, measure 10 times and take the average value.

[0076] 48-hour water retention rate: Weigh the hair after applying conditioner, place it in a 30℃ / 50%RH environment, and calculate the water loss rate.

[0077] Keratin peptide penetration depth: confocal Raman imaging (excitation wavelength 785 nm), labeled keratin peptide fluorescent probe (FITC).

[0078] Antibacterial rate of tea tree oil: qPCR was used to quantify the number of Malassezia furfur and the number of colonies before and after treatment was compared.

[0079] Double-trigger release efficiency: Franz diffusion cell (40℃ / pH5.5), HPLC determination of keratin peptide and tea tree oil release.

[0080] Conductive penetration depth: After electroosmotic actuation, confocal Raman imaging was used to determine the distribution depth of keratin peptides.

[0081] Electrical conductivity: Four-probe method (Keithley 2400), surface conductivity was measured after applying conditioner to hair.

[0082] Aroma retention rate (12h): headspace GC-MS analysis of the percentage of free aroma.

[0083] Storage stability (6 months): Dynamic light scattering (DLS) was used to measure the change in particle size, and HPLC was used to detect the retention of active ingredients.

[0084] Table 1 Performance of the hair conditioners of Examples 1 to 3 and Comparative Examples 1 to 7

[0085] From Table 1, we can see that: Comparative Example 1 (without quaternized sodium alginate): The friction coefficient increases (0.75): the lack of a cationic film layer cannot neutralize the static electricity on the hair, causing the hair scales to curl up more severely.

[0086] The water retention rate and penetration depth decrease: the charge gradient is destroyed, phosphorylated wheat protein cannot form a water-locking network, and the penetration of active ingredients is hindered.

[0087] Comparative Example 2 (without polyquaternium-67): Reduced flexibility (friction coefficient 0.68): incomplete charge gradient and uneven cation deposition lead to stiff hair.

[0088] The antibacterial rate decreased (88%): the release efficiency of tea tree oil decreased, and the loss of charge gradient weakened the regulation of scalp microenvironment.

[0089] Comparative Example 3 (non-phosphorylated wheat protein): The water retention rate drops sharply (59%): the three-dimensional water-locking network is lost and water is lost quickly.

[0090] The conductivity decreases (14 S / cm): the anion-cation electrostatic crosslinking is interrupted and the conductive network is incomplete.

[0091] Comparative Example 4 (without polyethylene glycol-150 distearate): Poor emulsion stability (particle size change 5%): the charge shielding effect disappears, and the liposomes and conductive microsheets aggregate and settle.

[0092] Reduced release efficiency (keratin peptide 70%): The instability of the emulsification system leads to a decrease in the liposome encapsulation rate.

[0093] Comparative Example 5 (without temperature-controlled liposomes): Failure of dual trigger release (keratin peptide 51%, tea tree oil 54%): the active ingredients only rely on passive diffusion, which is inefficient.

[0094] The antibacterial rate decreased (65%): Tea tree oil could not be released in a targeted manner, and the antibacterial effect was significantly reduced.

[0095] Comparative Example 6 (without conductive microsheet): Insufficient penetration depth (233 μm): Lacking electroosmotic drive, keratin peptides penetrated only by diffusion.

[0096] Very low conductivity (10 S / cm): The conductive network is missing and cannot coordinate liposome release.

[0097] Comparative Example 7 (without glyceryl glucoside + acetylated hyaluronic acid): The water retention rate and aroma retention rate decreased (58%, 50%): the dynamic moisturizing network was destroyed, and moisture and aroma were lost rapidly.

[0098] Fluctuation in repair depth (780 μm): Relying only on conductive penetration and lacking a moist environment to support repair efficiency.

[0099] It can be seen that Examples 1 to 3 are significantly better than all comparative examples in terms of core indicators such as flexibility, water retention rate, and repair depth through the linkage design of charge gradient synergy, intelligent dual-trigger release, conductive driven penetration, and dynamic moisturizing network. The performance of each comparative example is greatly reduced due to the lack of a single component, which verifies the necessity and synergistic effect of each component in the formula of the present invention.

[0100] In order to explore the safety of the conditioner, the conditioner obtained in Example 2 was subjected to a skin irritation test. The test method is as follows:

[0101] Patch test: Apply the conditioner to the back skin (0.02 g / cm²), apply it for 48 hours, and observe the reactions such as erythema and edema. Use it for 28 consecutive days and evaluate the irritation symptoms every day (scored according to ICDRG standards).

[0102] The final statistical result shows that the irritation index is ≤0.3 (no irritation), which is in line with ISO 10993-10 standard.

[0103] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0104] In addition, in the description of the specification of this application, the terms "include", "comprises", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0105] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A deep nourishing conditioner, characterized in that: The hair conditioner is composed of the following chemical components by mass fraction: quaternized sodium alginate: 2-4%, polyquaternium salt: 1-3%, phosphorylated wheat protein: 1-3%, polyethylene glycol-150 distearate: 0.5-2%, temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposomes: 5-6%, polyaniline nanofiber composite conductive microsheets: 0.1-0.3%, glycerol glucoside: 1.5-2.5%, acetylated hyaluronic acid: 0.5-1.5%, pH regulator ≤ 0.2%, emulsifier: 1-3%, thickener: 7-9%, lubricant: 2-4%, preservative: 0.5-0.7%, fragrance 0.3-0.5%, and the balance is deionized water; The temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid)-coated liposomes contain keratin peptides and tea tree oil in the liposomes; The polyaniline nanofiber composite conductive microsheet contains a polyethylene glycol-polylactic acid coating layer.

2. The deep nourishing conditioner according to claim 1, characterized in that The quaternary ammonium substitution degree of the quaternary ammonium sodium alginate is in the range of 60% to 80%, and the molecular weight is in the range of 500,000 to 800,000 Da; The polyquaternium salt is polyquaternium-67, and the cationic charge density is 0.8 to 1.2 meq / g; The phosphorylation substitution degree of phosphorylated wheat protein is ≥15% and the molecular weight is 10-30 kDa; The HLB value of polyethylene glycol-150 distearate is 8-10.

3. The deep nourishing conditioner according to claim 1, characterized in that: The temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposome has a liposome particle size of 80 to 120 nm, a coating layer thickness of 8 to 15 nm, and a mass ratio of keratin peptide and tea tree oil encapsulated in the liposome of (1 to 3):

1.

4. The deep nourishing conditioner according to claim 1, characterized in that The nanofiber diameter of the polyaniline nanofiber composite conductive microsheet is 50-80 nm, the length is 1-3 μm, the conductivity is ≥20 S / cm, and the thickness of the polyethylene glycol-polylactic acid coating layer is 200-500 nm.

5. The deep nourishing conditioner according to claim 1, characterized in that: The pH regulator is citric acid or lactic acid; The emulsifier is PEG-40 hydrogenated castor oil; The thickener is composed of xanthan gum and magnesium aluminum silicate, and the mass ratio of the xanthan gum to the magnesium aluminum silicate is 1:(1-3); The lubricant is dimethyl silicone oil; The preservative consists of phenoxyethanol and ethylhexylglycerin, and the mass ratio of the phenoxyethanol to the ethylhexylglycerin is 1:(1-3); The aromatic agent is natural plant essential oil embedded in beta-cyclodextrin.

6. A method for preparing the deep nourishing hair conditioner according to any one of claims 1 to 5, characterized in that: The method comprises: Obtaining the raw materials of the hair conditioner; Under stirring, adding the quaternized sodium alginate, the glycerol glucoside, the acetylated hyaluronic acid, the polyquaternium salt and the phosphorylated wheat protein into deionized water at a set temperature, and keeping the temperature to obtain an aqueous phase mixture; heating the polyethylene glycol-150 distearate, the emulsifier and the lubricant to a molten state to obtain an oil phase mixed liquid; The aqueous phase mixed liquid and the oil phase mixed liquid are subjected to high-speed homogenization treatment, and a thickener is added to obtain a first emulsion mixed liquid; Adding the temperature-controlled poly(N-isopropylacrylamide-co-acrylic acid)-coated liposomes and the polyaniline nanofiber composite conductive microsheet to the first emulsion mixture to obtain a second emulsion mixture; The pH regulator, the preservative and the fragrance are added to the second emulsion mixture to obtain the hair conditioner.

7. The method for preparing the deep nourishing hair conditioner according to claim 6, characterized in that: The high-speed homogenization treatment has a pressure of 5000-8000 psi, a cycle number of 3-5 times, and an emulsion particle size of ≤5 μm after homogenization.

8. The method for preparing the deep nourishing hair conditioner according to claim 6, characterized in that: The preparation method of the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposomes comprises: Linseed oil, lecithin and cholesterol were added into chloroform and then rotary evaporated to obtain lipid film; Dissolving keratin peptide and tea tree oil in phosphate buffer to obtain a hydrated solution; Under a nitrogen atmosphere, the hydration solution is added to the lipid membrane, followed by high-pressure homogenization to obtain liposomes; Under stirring, the liposome is added to a copolymer solution of N-isopropylacrylamide and acrylic acid, so that the copolymer is self-assembled on the surface of the liposome to obtain the temperature-controlled poly (N-isopropylacrylamide-co-acrylic acid) coated liposome.

9. The method for preparing the deep nourishing hair conditioner according to claim 8, characterized in that: The mass ratio of the flaxseed oil, the lecithin and the cholesterol is 7:(1-3):1; The mass concentration of the keratin peptide is 1-3%, and the mass concentration of the tea tree oil is 0.5-1.5%; The molar ratio of the N-isopropylacrylamide to the acrylic acid is 85:15; The mass ratio of the liposome to the copolymer is 5:

1.

10. The method for preparing the deep nourishing hair conditioner according to claim 6, characterized in that: The preparation method of the polyaniline nanofiber composite conductive microsheet comprises: The polyaniline nanofiber powder, polyethylene glycol-polylactic acid and dichloromethane are mixed to obtain a spinning solution; the mass concentration of the polyethylene glycol-polylactic acid in the spinning solution is 1-3%, and the mass ratio of the polyaniline nanofiber powder to the polyethylene glycol-polylactic acid is (1-3):1; The spinning solution is subjected to electrospinning and then pulverized to form a polyethylene glycol-polylactic acid coating layer with a set thickness on the surface of the polyaniline nanofiber to obtain the polyaniline nanofiber composite conductive microsheet; the voltage of the electrospinning is 18 to 20 kV, the propulsion rate is 0.7 to 0.9 mL / h, and the receiving distance is 10 cm.

Citation Information

Patent Citations

  • Alopecia-prevention hair-growth-promotion shampoo and preparation method thereof

    CN108078827A

  • Injectable composition for preventing hair loss or stimulating hair growth

    CN110312519A

  • Guar gum microcapsules

    CN113453655A

  • Hair-blacking composition, hair-blacking shampoo and preparation method and application of hair-blacking composition and hair-blacking shampoo

    CN113712890A

  • Hair cosmetic compositions containing a polyol, a saccharidic compound, and pectin, and methods of use

    FR3108508A1